Protection of Coastal Area by using Seawall & Mangrove Trees - Mr. Shubham Badave, Mr. Parth Aitwade, Mr. Ninad Chougule, Mr. Farhan Nadaf, Mr. Aniket Pujari (International Journal of New Media Studies: International Peer Reviewed Scholarly Indexed Journal, 2023)
The role of mangroves in protecting our coasts against natural hazards such as storms, tsunamis and coastal erosion has been widely acknowledged. Even so, the level of protection provided by mangroves remains subject to debate. Numerous mangrove restoration projects were instigated after the 2004 East Asian tsunami in the belief that replacing lost mangroves would reduce future risk, but others raised concerns that not all of these projects were well conceived, and that some might create greater risks by inducing a false sense of security. Can mangroves reduce waves and storm surges? How will they influence the forces of a tsunami? Do they actually contribute to stabilizing coasts and build-up of soils? Can they keep up with sea level rise?